General properties of water of Baidya fish pond, Tankisinwari, Nepal - Thapa, Ganesh Bahadur; Pal, Joydeb (Nepalese Journal of Biosciences, 2013)
In the present study, ranges and correlation among different physicochemical parameters viz., air temperature, water temperature, pH, turbidity, total dissolved solids, conductivity, dissolved carbon dioxide, ammonia, nitrate, dissolved oxygen, biological oxygen demand, chloride, total alkalinity, total hardness and phosphate were taken into consideration. The water quality of Baidya fish pond was normal except high fluctuation of chloride 1±0.241 to 29.84±0.260 mg/l and ammonia 1.55±0.088 to 18.7±0.061 mg/l during manuaring period and casual addition of wastes like toilet cleaners, caustic potash etc. Outbreak of epizootic ulcerative syndrome (EUS) was observed at the periphery of Baidya fish farm during winter months when polluted cold water from Koshi canal was added. The affected fishes developed several lesions around the body and fin rot. Due to sudden fall in dissolve oxygen, less than 4 mg/l during April and May, 2010 mass mortality of fishes Labeo rohita, Cirrhina mrigala, Hypothalamichthys molitrix, Aristichthys nobilis occurred. When chicken droppings were added in pond, ammonia was raised up to 18.7 mg/l which led to mass mortality of fish (Pangasius) during August. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7490 Nepalese Journal of Biosciences 2 : 55-63 (2012)